THE MANUSCRIPT BOOK IN THE GRAND DUCHY OF LITHUANIA EARLY IN THE 14th –MIDDLE OF THE 16th CENTURY: SPREAD AND FUNCTIONING - CICĖNIENĖ, RIMA (Knygotyra, 2015)
As far back as at the beginning of the 20th century, the book historian V. Biržiška noted that in the 15th century, GDL manuscript books not only did not disappear, but also expanded their repertoire. On the basis of the latest historical research and sources, the article aims to describe and assess the historical conditions, social and cultural processes that led to the manuscript book development, spread and functioning. The article bases its conclusions on the information from surviving manuscript books and archival sources. The paper analyses the phenomena that had a direct impact on the development of the book: the Christianization of the land, aspiration for the reunion of churches, the establishment and development of the sovereign estate and chancellery, the beginning of education. Thus, the history of GDL manuscript books is closely related to the first half of the 14th c. The establishment and development of the sovereign estate and the institutions of the Catholic Church contributed to the dissemination and functioning of Latin books. Due to teaching, writing culture was mastered throughout the country; the group of literate people, who wrote and read not only in Latin but also in Ruthenian grew rapidly. After the incorporation of Ruthenian lands, the GDL sought for a reunion of the churches. Creation of the Kiev metropolis with the center in Naugardukas, as well as the political, religious and cultural activities of the Orthodox metropolitan bishop led to the formation of the original manuscript book in the GDL. There appeard a group of persons (both Lithuanians and Ruthenians) who did intellectual work and had cultural needs. They not only became the main users of manuscript books, but also were their creators; they initiated and patronized writing books. In the GDL, New Latin and Ruthenian writing centers were established, and the repertoire of books expanded.
Keywords: ...